Determinants of Problems in Teenage Pregnancy - Hapisah, Hapisah; Rafidah, Rafidah; Sofia, Norlaila; Mahpolah, Mahpolah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the determinants or risk factors for pregnancy complications in adolescents. This type of research is quantitative analytical research with a case-control approach. The results of univariate analysis show that most respondents married at the age of 16-19 years (92%), and the remainder at the age of 12-15 years lived in rural areas (62%) and with their parents. (70). %), have low education (65.3%), have poor economic conditions (56%), and have anemia status (60%). The most frequently experienced pregnancy problems were constant vomiting and not wanting to eat (39.3%), while the least experienced were bleeding at the beginning or end of pregnancy and yellow eyes/skin (1.3% each). There are two variables related to teenage pregnancy problems, namely anemia status and knowledge about pregnancy. The most influential variable is anemia (p=0.000, OR: 3.995 (1.952-8.174). In conclusion, the impact of complications and deaths on women and children and the effect on future generations can be prevented. Keywords: Determinants, Teenage Pregnancy, Problems